The chronicle of Ibn al-Athir for the crusading period from al-Kamil fi’l-ta’rikh, part 2 : the years 541-589/1146-1193 the age of Nur al-Din and Saladin - Ibn al-Athir, Izz al-Din, 1160-1233 (Aldershot)
viii, 437 s.